Analisis Desain Spasial pada Bangunan Prefabrikasi: Residensial - Kusumah, Anita Febrianti (Program Studi Desain Interior Unikom, 2024)
Prefabricated residential innovation is producing large-scale building components from factory environmental standards and then assembled at the construction site, obtaining production process efficiency benefits with modular methods, adjusting to occupant needs from agreed design configurations. However, this innovation brings the dilemma of ownership being closer to manufacturing than occupants and the existence of standard limits in design improvisation. This study aims to evaluate the production results of prefabricated building components in its innovation to residents in planning occupancy, as it is known that the dilemma of prefabricated occupancy allows the risk of gaps between residents to places or known as placelessness. Qualitative methods with a case study approach have been used in this research through spatial design analysis by Ian Higgins by explaining physical elements through planning strategies, spatial requirements, and spatial compositions. The results of the study concluded that prefabricated buildings achieve occupancy factors; 1) Effective and functional, refers to meeting key needs and supporting activities, 2) Practical and optimal, refers to the design of space arrangements that prioritize comfort and convenience, 3) Compatible, refers to achieving room personalization according to needs and lifestyle.